“Estudio de factibilidad para la implementación de una lavadora de autos con un sistema automatizado en el cantón La Maná provincia de Cotopaxi, año 2023”. - Guanotuña Tipantuña, Freddy Lisandro (2023)
Ecuador has policies and programs based on the Plan Toda Una Vida that is aimed in promoting innovative ventures to strengthen dynamic development in the economy and to increase sources of employment. This research project is carried out with the aim of carrying out a feasibility study for implementing an express washing machine with an automated coin system in La Maná canton, Cotopaxi province. The study arises from the need that citizens who provide light cargo transport service have in order to wash vehicles permanently, quickly, and economically. Therefore, this need becomes a business opportunity. For the purpose and fulfillment of the proposed objective, the following aspects are taken into account: a market study where a high amount of acceptance was determined, a technical study that determined the operation to optimize resources, and an economic study that analyzed the ability to generate profits from the use of resources. Once the results were obtained, it was possible to conclude that the implementation of the washing machine in La Maná canton is viable, according to the fact that there is a current supply of 1,968 hours per year and an unsatisfied demand of 89,136 hours, so evidencing a wide market for this proposal. Firstly, it was projected to be carried out with 1% equivalent to 12,096 vehicle washes. Through the technical study it was possible to determine the macro, meso, and micro location, flowchart, infrastructure distribution, and organizational structure. The total investment required was $28.211,92. The net profit that is intended to be obtained in the first year was $2.271,02, with an IRR of 15,54%. The implementation of the car washer with an automated system is recommended, which will benefit the social and economic sphere of La Maná canton. With the current investigation on the implementation of the car washer with an automated system, the students of the UTC, the transport companies, vehicle owners, and state entities will benefit from the collection of taxes.